Compound Evolutionary History of the Rhesus Macaque Mhc Class I B Region Revealed by Microsatellite Analysis and Localization of Retroviral Sequences - Doxiadis, Gaby G. M.; Heijmans, Corrine M. C.; Bonhomme, Maxime; Otting, Nel; Crouau-Roy, Brigitte; Bontrop, Ronald E. (PLOS ONE, 2009)
In humans, the single polymorphic B locus of the major histocompatibility complex is linked to the microsatellite MIB. In rhesus macaques, however, haplotypes are characterized by the presence of unique combinations of multiple B genes, which may display different levels of polymorphism. The aim of the study was to shed light on the evolutionary history of this highly complex region. First, the robustness of the microsatellite MIB-linked to almost half of the B genes in rhesus macaques (Mamu-B)–for accurate B haplotyping was studied. Based on the physical map of an established haplotype comprising 7 MIB loci, each located next to a certain Mamu-B gene, two MIB loci, MIB1 and MIB6, were investigated in a panel of MHC homozygous monkeys. MIB1 revealed a complex genotyping pattern, whereas MIB6 analysis resulted in the detection of one or no amplicon. Both patterns are specific for a given B haplotype, show Mendelian segregation, and even allow a more precise haplotype definition than do traditional typing methods. Second, a search was performed for retroelements that may have played a role in duplication processes as observed in the macaque B region. This resulted in the description of two types of duplicons. One basic unit comprises an expressed Mamu-B gene, adjacent to an HERV16 copy closely linked to MIB. The second type of duplicon comprises a Mamu-B (pseudo)gene, linked to a truncated HERV16 structure lacking its MIB segment. Such truncation seems to coincide with the loss of B gene transcription. Subsequent to the duplication processes, recombination between MIB and Mamu-B loci appears to have occurred, resulting in a hyperplastic B region. Thus, analysis of MIB in addition to B loci allows deciphering of the compound evolutionary history of the class I B region in Old World monkeys.